2011
DOI: 10.1093/aob/mcr072
|View full text |Cite
|
Sign up to set email alerts
|

Linking water stress effects on carbon partitioning by introducing a xylem circuit into L-PEACH

Abstract: This work opens the way to a new field of modelling where complex interactions between water transport, carbohydrate allocation and physiological functions can be simulated at the organ level and describe functioning and behaviour at the tree scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 38 publications
1
33
0
Order By: Relevance
“…The results of this study also confirmed that the vegetative growth was more strongly affected by water deficit than fruit growth. It would be interesting to include these results into functional-structural models of tree growth which have been developed for the peach tree [ 50 , 51 ] to provide more details of the whole-tree functioning in relation to water deficit.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study also confirmed that the vegetative growth was more strongly affected by water deficit than fruit growth. It would be interesting to include these results into functional-structural models of tree growth which have been developed for the peach tree [ 50 , 51 ] to provide more details of the whole-tree functioning in relation to water deficit.…”
Section: Discussionmentioning
confidence: 99%
“…In its current version, it combines a detailed description of the 3D plant architecture with a mechanistic representation of selected physiological functions, including nutrient assimilation, transport, and allocation (Da Silva et al, 2011). However, fruit sink growth, is described as a simple function of local carbon and water availabilities, regardless of fruit developmental stages and metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the water potential values were all higher in es1-1 than in the wild type in various tissues, including roots, stems, leaves, and sheath, which indicated that the ability to transport water was stronger in es1-1 than in the wild type ( Fig. 8G; Da Silva et al, 2011). Therefore, our results indicate that es1-1 mutants have an enhanced ability to transport water.…”
Section: Es1 Affects the Density Of Leaf Stomata In Ricementioning
confidence: 65%